Factors That Influence Consumer Attitude Towards Purchase Intention On The Shopee Application Live Streaming - Raihan Maulana Muthar; Erlita Ridanasti (Cita konsultindo, 2025)
This study aims to examine several factors that can influence consumer behavior or attitudes towards purchasing interest in live streaming on the Shopee application. This study is based on the phenomenon of live stream shopping on the Shopee marketplace where in the live streaming shopping session there is an interaction between the audience and influencers through live stream and several factors that can potentially trigger purchasing interest in the minds of consumers. Several factors that will be studied are influencers, price discounts, interactions, and audience attitudes towards the emergence of purchasing interest in them. This study uses a quantitative statistical approach with a data collection method using a questionnaire and obtained 200 research respondents. The statistical analysis used in this study is SEM PLS with the aim of studying the influence between research construct variables. The findings of this study state that influencers, price discounts, and interactions established with the audience have a positive and significant effect on audience attitudes. This audience attitude has a positive and significant effect on purchasing interest through Shopee Live Stream Shopping. The results of this study indicate that increasing interaction with the audience, utilizing the right influencers, and offering attractive price discounts during live streaming sessions on Shopee can increase the audience's positive attitude, which ultimately drives consumer purchasing interest.